Weather on the Air A History of Broadcast Meteorology - Henson, Robert. (American Meteorological Society : Imprint: American Meteorological Society, 2010)
From low humor to high drama, TV weather reporting has encompassed an enormous range of styles and approaches, triggering chuckles, infuriating the masses, and at times even saving lives. In Weather on the Air, meteorologist and science journalist Robert Henson covers it allthe people, technology, science, and show business that combine to deliver the weather to the public each day. Featuring the long-term drive to professionalize weathercasting; the complex relations between government and private forecasters; and the effects of climate-change science and the Internet on todays broadcasts. With dozens of photos and anecdotes illuminating the many forces that have shaped weather broadcasts over the years, this engaging study will be an invaluable tool for students of broadcast meteorology and mass communication and an entertaining read for anyone fascinated by the public face of weather.